Conceptualizing hybrid intelligent service ecosystems - Christian Bartelheimer; Daniel Heinz; Sarah Hönigsberg; Dominik Siemon; Mahei Manhai Li; Timo Strohmann; Jens Poeppelbuss; Christoph Peters (Electronic Markets, 2025)
With the proliferation of artificial intelligence (AI) technologies, the collaboration of human and AI actors in value co-creation processes permeates various application domains. In this conceptual paper, we integrate concepts from human-AI collaboration and service research and present a conceptual framework for hybrid intelligent service ecosystems (HISE). The framework extends the existing conceptualizations of service ecosystems as put forward by the service-dominant logic (S-D logic) by emphasizing how actors deliberately configure human and artificial agencies to co-create value via hybrid intelligent service exchange and how this impacts ecosystem formation and evolution. Our conceptualization highlights that value co-creation in HISE is guided and facilitated by shared resources and institutional arrangements, which differ from previous service ecosystems through the emergence of hybrid agency. We demonstrate the applicability of our framework with five illustrative HISE scenarios and provide five theoretical propositions. Our findings extend existing knowledge by theorizing on how to incorporate hybrid intelligence into value co-creation processes. Thereby, we provide a foundation for future interdisciplinary research on human-AI collaboration at the intersection of information systems, human–computer interaction, and service research with S-D logic as a unifying theoretical lens.
Keywords: M15; 620; Hybrid intelligence; Service ecosystems; Value co-creation; Artificial intelligence